Validitas Konstruk Alat Ukur College Academic Self-efficacy Scale pada Mahasiswa - Musyafirah, Tiara Dewi; Tira, Usagi Alifa; Rosalia, Vinka; Fajriyah, Zahyrina Akhsanti; Nurmalitasari, Femmi (Universitas Negeri Malang, 2024)
Academic self-efficacy refers to an individual's ability to engage in learning activities to achieve academic goals. Measuring academic self-efficacy among students is necessary to gain an overview of the self-efficacy they possess and to identify appropriate intervention steps to support academic success. There are several instruments for measuring academic self-efficacy, one of which is the College Academic Self-Efficacy Scale (CASES). This instrument was adapted into Indonesian in 2022, but its measurement has been limited to content validity. This study aims to re-examine the construct validity of the adapted CASES measure to determine whether each factor aligns with the cultural context. The testing will be conducted through a quantitative research design. The sampling technique will use purposive sampling with a total sample of 116 respondents, who are active students at universities in Indonesia. Data analysis will utilize the JASP application to perform Confirmatory Factor Analysis (CFA). Psychometric results indicate that the adapted CASES has not achieved a fit model. This suggests that the CASES measure still needs further development. AbstrakEfikasi diri akademik adalah kemampuan yang dimiliki individu untuk menjalankan aktivitas belajar untuk mencapai tujuan akademik. Pengukuran terkait efikasi akademik di kalangan mahasiswa diperlukan agar membantu melihat gambaran efikasi akademik yang dimiliki mahasiswa serta untuk mengindentifikasi langkah intervensi yang tepat dalam menunjang keberhasilan akademik. Terdapat beberapa instrumen untuk pengukuran academic self-esteem, salah satunya College Academic Self-Efficacy Scale (CASES). Instrumen tersebut telah diadaptasi ke dalam Bahasa Indonesia pada tahun 2022, namun masih terbatas pada pengukuran validitas isi. Penelitian ini bertujuan untuk menguji kembali validitas konstruk dari alat ukur CASES yang telah diadaptasi agar diketahui setiap faktor yang ada sesuai konteks budaya. Pengujian dilakukan melalui desain penelitian kuantitatif. Teknik pengambilan sampel menggunakan purposive sampling dengan jumlah sampel 116 responden yang merupakan mahasiswa aktif di universitas di Indonesia. Analisis data menggunakan aplikasi JASP untuk melakukan Confirmatory Factor Analysis (CFA). Hasil psikometri menunjukkan bahwa CASES yang telah diadaptasi belum mendaptkan model yang fit. Hal ini menunjukkan bahwa alat ukur CASES masih perlu untuk dikembangkan lebih lanjut.